1984
DOI: 10.1128/jvi.50.2.301-308.1984
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of avian leukosis virus-induced hyperlipidemia

Abstract: Rous-associated virus 7 (RAV-7) is a subgroup C avian leukosis virus which does not transform cells in vitro or carry an oncogene. When injected into 1-day-old hatched chicks, RAV-7 causes a low incidence of lymphoid leukosis after a latent period of several months. In contrast, infection of 10-day-old chicken embryos with RAV-7 leads to a disease syndrome characterized by stunting, obesity, atrophy of the bursa and the thymus, high triglyceride and cholesterol levels, reduced thyroxine levels, and increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The strains of ALV-C include RAV-7, RAV-49, B77 and Pr RSV-C. Sandelini & Estola (1974) isolated ALV-C in Finnish breeding flocks and reported that the antibody against ALV-C was widespread in Finland at that time. In natural or experimental infection, RAV-7 and RAV-49 mainly cause stunting, obesity, hypothyroidism, hyperinsulinaemia, alterations in lipid metabolism, meningoencephalomyelitis and a low incidence of lymphoid leukosis , 1984Heidrich et al, 1987;Whalen et al, 1988). The severity of these isolates, however, appears to be strain dependent (Karakoz et al, 1980;Smith & Schmidt, 1982;Stepanets et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The strains of ALV-C include RAV-7, RAV-49, B77 and Pr RSV-C. Sandelini & Estola (1974) isolated ALV-C in Finnish breeding flocks and reported that the antibody against ALV-C was widespread in Finland at that time. In natural or experimental infection, RAV-7 and RAV-49 mainly cause stunting, obesity, hypothyroidism, hyperinsulinaemia, alterations in lipid metabolism, meningoencephalomyelitis and a low incidence of lymphoid leukosis , 1984Heidrich et al, 1987;Whalen et al, 1988). The severity of these isolates, however, appears to be strain dependent (Karakoz et al, 1980;Smith & Schmidt, 1982;Stepanets et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As lipids are critical to the biology of enveloped viruses, some of these viruses modulate the host-cell lipid metabolism to their advantage, by up-or down-regulating their lipid synthesis [2,8,16,28]. However, recent reports have demonstrated the involvement of lipids in the cell biology of a non-enveloped, double-stranded RNA virus, the rotavirus, as well [3,5,6,13,33].…”
Section: Introductionmentioning
confidence: 99%
“…25 Although the vast majority of the research on these retroviruses has focused on their oncogenic properties, several studies have focused on their nonneoplastic effects and pathogenesis in younger chickens. Viruses in ALV subgroups A, B, C, and D produced stunting in growing chickens associated with a lymphocytic thyroiditis and lowered circulating thyroxine levels, with the most severe effects associated with ALV subgroup C. 7,8 RAV-1—a subgroup A ALV—induced myocarditis, right-sided heart failure, and ascites syndrome in immature chickens and was associated with the formation of viral matrix inclusion bodies in cardiac myocytes. 15,16 An ALV produced by a lymphoid leukosis cell line also induced ascites when inoculated into immature chickens.…”
mentioning
confidence: 99%